Hibiscus Asper (Raman Kogi) Fibre Use as a Sorbent for Oil Spill Clean in Water Body - N. E. Alpha; J. T. Barminas; S. A. Osemeahon (Archives of Current Research International, 2019)
This research aimed at investigating the possibility of using Imperata cylindrical fibre as a sorbent for oil spill clean-up. The acetylation was carried out in a free solvent system under mild conditions using acetic anhydride, in the presence of calcium chloride as a catalyst, at a temperature of 100oC for 3 hours. The crude oil and the Hibiscus asper sorbent were characterised, the sorption behaviours studied were found to increase with an increase in weight per gain percent (WPG%). The WPG% and oil sorption capacity indicated the success of acetylation. Fourier transform infrared spectroscopy (FT-IR) was used for the analysis of unmodified and modified Hibiscus asper sorbent to further examine the success of acetylation. In the spectra of FT-IR of the acetylated Hibiscus asper material evidence of acetylation is clearly proven by, the enhancement of 1755 cm-1, as 1755.31-1715.97 cm-1 which are carbonyl C=O stretching of esters, the enhancement of 1494.97 -1403.35 cm-1 of (C-H bond in –O(C=O)-CH3 and the appearance of 1154.69- 1154.43 cm-1 which is a C=O stretching of acetyl group. The values for the correlation coefficient (R2) showed that the model fitted the Langmuir isotherm (R2 Hibiscus asper 0.99) better than the Freundlich isotherm, indicating that the adsorption process was a monolayer. The higher oil sorption capacity shown by the modified Hibiscus asper sorbent compared to the lower oil sorption capacity of unmodified indicated that the modified Hibiscus asper sorbent can substitute for synthetic fibres and recommended for oils spill clean-up in contaminated environments.